Death penalty in so-called donetsk and luhansk Peoples republics: arbitrary excesses Of pro-russian rebels or “back to the sources”? : ст. - Makarchuk, V.; Terlyuk, I. et. al. (Access to Justice in Eastern Europe, 2022)
The article raises the issue of formal “justification” and direct practice of the death penalty in certain areas of Donetsk and Luhansk regions (hereinafter ORDLO) of Ukraine affected by the uprising and subjected to Russian aggression. The first cases of executions of Ukrainian patriots by rebels and their Russian curators (Igor Girkin, Arseniy Pavlov (Motorola), etc.) date back to April 2014. The massacres were carried out mainly out of court – on the orders of field commanders. However, collective courts were seldom held for propaganda purposes, where “saboteurs” and banal marauders and rapists were sentenced by show of hands. In August 2014, the so-called “Criminal Code” was “enacted”, Article 58 of which established the death penalty for “especially serious crimes” without specifying their list. Instead, life imprisonment officially became the highest punishment in the self-proclaimed neighbouring Luhansk People’s Republic. At the same time, the leadership of both “republics” announced that the current legislation of the Russian Federation is taken as the basis of their criminal legislation. Instead, death sentences are handed down and enforced de facto out of court in both the DPR and the LPR. This practice of dividing death sentences into relatively small de jure and mass ones, de facto uncontrolled sentences (by decision of field commanders or security officials), has been characteristic of Soviet practice since the dawn of the 20th century – late 1917 to be precise. The concern of global human rights structures with the issues of observance of the fundamental human right – the right to life – in the ORDLO was reflected in a special Report of the Office of the UN High Commissioner for Human Rights (2020). It is noted that the death penalty is maintained in temporarily occupied territories, and sentences are handed down and enforced.
Keywords: death penalty in the RSFSR and the USSR; смертна кара в РРФСР і СРСР